Transitivity Analysis of "sonet 12" by William Shakespeare Linguistics Studies - ilham sahdi lubis (Jurnal Education and Development, 2017)
This paper entitled “Transitivity Analysis Of “Sonet 12” by William Shakespeare: Linguistics Studies. This study is also focused on revealing what kinds of processes and circumstances that the text in Sonet 12 used the transitivity system. This study was a library research. This study used a case study research design. The data was text in Sonet 12. The text was analyzed using the Halliday (1985, 1994) theory. The findings of this study show that the text found a material, verbal and behavioral process whereas the occurrences of circumstances tend to be equal.